MOF (Metal Organic Framework) compound with photothermal conversion performance as well as preparation method and application thereof

By growing Ni3 (HHTP) 2 nanorods on the surface of MIL-101 (Cr), a MOFs material is formed to form a MOF composite with photothermal conversion performance, solving the problems of poor thermal conductivity and insufficient photothermal performance of MOFs material, and achieving efficient water Molecular adsorption and desorption reduce energy consumption and improve the energy efficiency of air water intake systems.

CN119236893APending Publication Date: 2025-01-03BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411396564.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing MOFs materials used for air water withdrawal have poor thermal conductivity and do not have light absorption and light-thermal conversion properties, so they are difficult to directly utilize in solar-powered adsorption air water withdrawal. They usually need to rely on external heat sources to achieve desorption.

Method used

Using MIL-101(Cr) as the core-shell structure, Ni3(HHTP)2 nanorods are grown in situ on its surface to form a MOF complex with a core-shell structure, and the π-π conjugated structure of Ni3(HHTP)2 is used. Convert light energy into heat energy to achieve photothermal conversion performance.

Benefits of technology

It improves the adsorption and desorption efficiency of water molecules, reduces dependence on external heat sources, reduces system energy consumption, improves the energy efficiency and economy of the entire water withdrawal process, and shows excellent light absorption, photo-heat conversion and heat conduction properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236893A_ABST
    Figure CN119236893A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adsorption materials for taking water from air, in particular to an MOF (Metal Organic Framework) compound with photothermal conversion performance and a preparation method and application thereof. According to the preparation method, MIL-101 (Cr) with high hygroscopicity is selected as the center of a core-shell structure, 2, 3, 6, 7, 10, 11-hexahydroxy triphenylene with a photothermal effect is taken as a ligand, Ni3 (HHTP) 2 is grown on the surface of the MIL-101 (Cr) in situ, and the MOF compound with the core-shell structure is obtained. The MOF compound disclosed by the invention not only can efficiently adsorb water molecules in air, but also can quickly heat after absorbing sunlight due to the unique photothermal effect of the MOF compound, so that the desorption process of the water molecules is promoted. Due to the photo-thermal performance of the MOF compound, the dependence on an external heat source is remarkably reduced, the energy consumption of the system is reduced, and the energy efficiency and economical efficiency of the whole water taking process are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air water absorption materials, and in particular to a MOF composite with light-to-heat conversion performance, and a preparation method and application thereof. Background Art

[0002] The shortage of freshwater resources has become an urgent problem worldwide, which not only threatens the sustainable development of human society, but also affects the balance of the ecosystem. With the continuous growth of population and the acceleration of industrialization, traditional water resource acquisition methods, including groundwater extraction, river interception, and seawater desalination, have been unable to meet the growing demand for water. In order to meet the needs of human survival and sustainable development, centralized water supply systems are currently the main way to supply water resources. However, in special terrain areas such as deserts, isolated islands, and rugged mountains, the implementation of centralized water supply systems faces many challenges due to factors such as remote geographical location, harsh climatic conditions, and high economic costs. As a renewable water source that is often overlooked, the potential water resource value of water vapor resources in the atmosphere has not been fully explored. If the moisture in the atmosphere can be effectively collected, it will have a positive impact on alleviating the water resource pressure in special terrain areas. At present, surface cooling technology is a relatively mature technology in the field of air water extraction, but its water production efficiency is unstable and it consumes a lot of energy, so its application is subject to certain restrictions. Solar adsorption air water extraction technology, as an emerging way of obtaining water resources, uses highly hygroscopic adsorbents to capture moisture from the air, uses solar energy as a driving force, and releases and collects moisture through thermal desorption. It has the advantages of not being restricted by geographical location, having little environmental impact, and low energy consumption. It provides a new technical approach to solving water resource problems in special terrain areas.

[0003] In the field of solar-driven adsorption-type air water extraction technology, the adsorption and desorption performance of water molecules is the core property of the adsorbent material. The ideal adsorbent should have fast adsorption and desorption rate, high water absorption capacity, stable cycle, and efficient light absorption and photothermal conversion performance. In this field, researchers have developed a variety of composite adsorbents based on gel and cellulose. These composites are usually prepared by compounding or mixing polymers with photothermal response components such as graphene oxide, carbon nanotubes, graphene, etc. However, the adsorption and desorption rate of composite adsorbents based on gel and cellulose is slow and it is difficult to maintain a stable adsorption and desorption cycle process. In addition, the uneven distribution of photothermal materials during the preparation of composite materials may reduce the overall light absorption efficiency and thermal conductivity efficiency of the material, and even cause overheating in local areas, which may not only damage the material itself, but also affect the efficiency of the entire water extraction system.

[0004] Metal-Organic Frameworks (MOFs) materials have become a hot topic of research due to their unique pore structure, high specific surface area and adjustable chemical composition. MOFs materials have shown great potential in the fields of gas adsorption, separation and storage. As water adsorbents, MOFs materials have the advantages of fast adsorption and desorption rates and directionally adjustable adsorption humidity. However, most MOFs have poor thermal conductivity and do not have light absorption and photothermal conversion properties. Therefore, they are difficult to be directly used in solar-driven adsorption air water extraction and usually rely on external heat sources for desorption. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a MOF composite with photothermal conversion performance and a preparation method and application thereof, so as to at least solve the problem that the existing MOFs materials used for air water extraction have poor thermal conductivity and do not have light absorption and photothermal conversion performance, are difficult to be directly used in solar-driven adsorption air water extraction, and usually need to rely on external heat sources to achieve desorption.

[0006] The present invention solves the above technical problems by the following technical means:

[0007] In the first aspect, the present invention provides a MOF composite having light-to-heat conversion performance, wherein the MOF composite is based on MIL-101 (Cr) as a core, Ni 3 (HHTP) 2 The nanorods are core-shell structures, and the Ni 3 (HHTP) 2 Nanorods attached to MIL-101(Cr) particles.

[0008] In combination with the first aspect, in some embodiments, the MIL-101(Cr) is an octahedral crystal structure with a smooth surface.

[0009] In combination with the first aspect, in some embodiments, the MOF composite comprises the following raw materials: MIL-101(Cr), 2,3,6,7,10,11-hexahydroxytriphenylene and Ni(CH 3 COO 2 ·4H 2 O, the MIL-101 (Cr), 2,3,6,7,10,11-hexahydroxytriphenylene and Ni (CH 3 COO 2 ·4H 2 The molar ratio of O is 2:1:1.

[0010] In a second aspect, the present invention provides a method for preparing a MOF composite having light-to-heat conversion performance, comprising the following steps:

[0011] Weigh 2,3,6,7,10,11-hexahydroxytriphenylene and MIL-101(Cr) respectively, dissolve them in a mixed solvent consisting of deionized water and n-propanol, drop N,N-dimethylacetamide into it, and perform ultrasonication for 10 to 30 minutes to obtain solution A;

[0012] Ni(CH 3 COO 2 ·4H 2 O is dispersed in a mixed solvent consisting of deionized water and n-propanol, and ultrasonically mixed to obtain solution B;

[0013] Solution A and solution B were mixed, stirred at 55-70°C for 2-5 hours, cooled to room temperature, centrifuged, and the obtained solid was dispersed in the mixed solvent again, and 2,3,6,7,10,11-hexahydroxytriphenylene, Ni(CH 3 COO 2 ·4H 2 O, drop N,N-dimethylacetamide, ultrasonicate for 5-10 min, then stir at 50-65 °C for 2-5 h, cool to room temperature, centrifuge, and wash the solid product with deionized water and acetone three times, respectively, and dry to obtain a MOF composite.

[0014] In combination with the second aspect, in some embodiments, the MIL-101(Cr), 2,3,6,7,10,11-hexahydroxytriphenylene and Ni(CH 3 COO 2 ·4H 2 The total molar ratio of O is 2:1:1.

[0015] In combination with the second aspect, in some embodiments, in the mixed solvent, the volume ratio of deionized water to n-propanol is 1:1.

[0016] In conjunction with the second aspect, in some embodiments, the preparation method of the MIL-101(Cr) is as follows:

[0017] Weigh Cr(NO) 3 9H 2 O is dissolved in deionized water to obtain a metal salt solution, terephthalic acid is uniformly dispersed in N,N-dimethylformamide to obtain an organic solution, the metal salt solution and the organic solution are mixed and stirred, and hydrofluoric acid is added with stirring, and heated at 150-180°C for 12-24h, cooled to room temperature, filtered to remove the solvent, and the obtained solid product is dispersed in deionized water, placed at 60-80°C for reaction for 2-4h, cooled to room temperature, centrifuged to remove the solvent, and then washed with DMF and dried to obtain MIL-101(Cr).

[0018] In conjunction with the second aspect, in some embodiments, the Cr(NO) 3 9H 2 The molar ratio of O to terephthalic acid is 1:1.

[0019] In conjunction with the second aspect, in some embodiments, per mole of Cr(NO) 3 9H 2 O add 18-22 mL of hydrofluoric acid dropwise.

[0020] In a third aspect, the present invention further provides the use of the MOF composite described in the first aspect or the MOF composite prepared by the preparation method described in the second aspect in adsorption-type air water extraction.

[0021] The MOF composite with photothermal conversion performance of the present invention selects MIL-101 (Cr) with high hygroscopicity as the center of the core-shell structure, uses 2,3,6,7,10,11-hexahydroxytriphenylene with photothermal effect as a ligand, and in-situ grows Ni on the surface of MIL-101 (Cr). 3 (HHTP) 2 , a MOF composite with a core-shell structure is obtained. MIL-101(Cr) has a high specific surface area and a unique pore structure, so it has a high adsorption capacity and acts as a water adsorption center; Ni 3 (HHTP) 2 It is a two-dimensional conductive MOF, the π-π conjugated structure in its ligand HHTP can broaden the light absorption range of the molecule, and can effectively convert light energy into heat energy through the migration and vibration of electrons. The MOF complex of the present invention can not only efficiently adsorb water molecules in the air, but also its unique photothermal effect enables it to quickly heat up after absorbing sunlight, thereby promoting the desorption process of water molecules. The photothermal performance of the MOF complex of the present invention significantly reduces the dependence on external heat sources, reduces the energy consumption of the system, and improves the energy efficiency and economy of the entire water extraction process.

[0022] After testing, the MIL-101(Cr)@Ni 3 (HHTP) 2 The composite exhibits strong absorption capacity of 70% to 90% in the entire solar wavelength band. 3 (HHTP) 2 The thermal conductivity of the composite is much higher than that of common MOFs (MOF-801, MOF-303); MIL-101(Cr)@Ni under light conditions 3 (HHTP) 2 The mass of the complex decreases rapidly, and the desorption amount is calculated to be 0.58 gg within 800 s. –1The desorption efficiency is 83%, indicating that MIL-101(Cr)@Ni 3 (HHTP) 2 The composite has excellent light absorption, photothermal conversion and thermal conductivity properties; the adsorption saturated MIL-101(Cr)@Ni 3 (HHTP) 2 The composite can reach desorption equilibrium in less than 30 minutes, with a desorption efficiency of up to 82.8%. In the subsequent adsorption and desorption cycles, the photothermal desorption efficiency is stable at 90%. After multiple cycle tests, MIL-101(Cr)@Ni 3 (HHTP) 2 It not only exhibits excellent water adsorption capacity, but also demonstrates efficient photothermal desorption performance and excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is Ni in Example 3 3 (HHTP) 2 , MIL-101(Cr), MIL-101(Cr)@Ni 3 (HHTP) 2 SEM images of the composite;

[0024] Figure 2 It is MIL-101(Cr)@Ni 3 (HHTP) 2 XPS full spectrum of the composite;

[0025] Figure 3 It is MIL-101(Cr)@Ni 3 (HHTP) 2 Complex with Ni 3 (HHTP) 2 High-resolution Ni 2p in crystals 3 / 2 Spectrum graph;

[0026] Figure 4 It's Ni 3 (HHTP) 2 、MIL-101(Cr) and MIL-101(Cr)@Ni 3 (HHTP) 2 N of the complex 2 Isothermal adsorption-desorption curves;

[0027] Figure 5 It's Ni 3 (HHTP) 2 、MIL-101(Cr) and MIL-101(Cr)@Ni 3 (HHTP) 2Pore ​​size distribution of the composite;

[0028] Figure 6 It's Ni 3 (HHTP) 2 、MIL-101(Cr) and MIL-101(Cr)@Ni 3 (HHTP) 2 Water vapor static isothermal adsorption-desorption curve of the composite;

[0029] Figure 7 MIL-101(Cr)@Ni at different relative humidity 3 (HHTP) 2 Adsorption rate of the complex;

[0030] Figure 8 It is MIL-101(Cr)@Ni 3 (HHTP) 2 Absorbance test result diagram of the complex;

[0031] Fig. 9 It is MIL-101(Cr)@Ni after light exposure 3 (HHTP) 2 Variation of the maximum temperature of the composite surface with time;

[0032] Fig.10 It is common MOF (MOF-801, MOF-303) and MIL-101(Cr), as well as MIL-101(Cr)@Ni 3 (HHTP) 2 Thermal conductivity test results of the composite;

[0033] Fig.11 It is MIL-101(Cr)@Ni 3 (HHTP) 2 The graph of the desorption amount of the composite changing with time;

[0034] Fig.12 It is MIL-101(Cr)@Ni 3 (HHTP) 2 The relationship between the water adsorption amount of the composite and time;

[0035] Fig.13 It is MIL-101(Cr)@Ni 3 (HHTP) 2 Adsorption-desorption cycle diagram of the complex. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials, equipment or instruments used, if no manufacturer is specified, are all conventional products that can be purchased on the market.

[0038] The present invention selects MIL-101 (Cr) with high hygroscopicity as the center of the core-shell structure, uses 2,3,6,7,10,11-hexahydroxytriphenylene (2,3,6,7,10,11-hexahydroxytriphenylene, HHTP) with photothermal effect as a ligand, and in-situ grows nanorods Ni on the surface of MIL-101 (Cr) with a smooth octahedral morphology crystal structure. 3 (HHTP) 2 , a MOF composite with a core-shell structure is obtained. MIL-101(Cr) has a high specific surface area and a unique pore structure, so it has a high adsorption capacity and acts as a water adsorption center; Ni 3 (HHTP) 2 It is a two-dimensional conductive MOF, the π-π conjugated structure in its ligand HHTP can broaden the light absorption range of the molecule, and can effectively convert light energy into heat energy through the migration and vibration of electrons. The MOF complex of the present invention can not only efficiently adsorb water molecules in the air, but also its unique photothermal effect enables it to quickly heat up after absorbing sunlight, thereby promoting the desorption process of water molecules. The photothermal performance of the MOF complex of the present invention significantly reduces the dependence on external heat sources, reduces the energy consumption of the system, and improves the energy efficiency and economy of the entire water extraction process.

[0039] For details, please refer to Examples 1-4:

[0040] Example 1

[0041] The preparation method of the MOF composite with light-to-heat conversion performance of this embodiment is as follows:

[0042] (1) Preparation of MIL-101(Cr)

[0043] Weigh 5mmol Cr(NO) 3 9H 2O was dissolved in 20 mL of deionized water to obtain a metal salt solution. 5 mmol of terephthalic acid was evenly dispersed in 2 mL of N,N-dimethylformamide to obtain an organic solution. The metal salt solution and the organic solution were mixed and stirred, and hydrofluoric acid was added dropwise while stirring. 3 9H 2 O was added dropwise with 3.6 microliters of hydrofluoric acid. After the addition was completed, the mixture was heated at 150°C for 24 hours. After cooling to room temperature, the solvent was filtered to remove the solvent. The obtained green solid product was dispersed in deionized water and centrifuged. The deionized water washing and centrifugation were repeated three times. The obtained solid product was placed at 60°C for reaction for 2 hours. After cooling to room temperature, the solvent was removed by centrifugation. The solid product was dispersed in DMF and centrifuged, and dried at 80°C to obtain MIL-101 (Cr).

[0044] (2) Preparation of MIL-101(Cr)@Ni 3 (HHTP) 2 Compound

[0045] A mixed solvent was prepared according to a volume ratio of deionized water to n-propanol of 1:1. 5 mmol of 2,3,6,7,10,11-hexahydroxytriphenylene and 20 mmol of MIL-101(Cr) were dissolved in 120 mL of the mixed solvent, and 8 mL of N,N-dimethylacetamide was added dropwise, and ultrasonication was performed for 10 min to obtain solution A.

[0046] 5mmol Ni(CH 3 COO 2 ·4H 2 O was dispersed in 60 mL of the mixed solvent and mixed by ultrasonication to obtain solution B.

[0047] Solution A and solution B were mixed, stirred at 55 °C for 2 h, cooled to room temperature, and centrifuged to remove the solvent. The obtained dark blue solid was dispersed again in 100 mL of mixed solvent, and 5 mmol 2,3,6,7,10,11-hexahydroxytriphenylene and 5 mmol Ni(CH 3 COO 2 ·4H 2 O, 8 mL of N,N-dimethylacetamide was added dropwise, ultrasonicated for 5 min and allowed to stand for 10 min, then stirred at 50 °C for 2 h, cooled to room temperature, centrifuged to remove the solvent, and the obtained solid product was washed three times with deionized water and acetone, respectively, and dried at 80 °C to obtain a blue-black solid MIL-101(Cr)@Ni 3 (HHTP) 2 Composite, namely MOF composite.

[0048] Example 2

[0049] The preparation method of the MOF composite with light-to-heat conversion performance of this embodiment is as follows:

[0050] (1) Preparation of MIL-101(Cr)

[0051] Weigh 5mmol Cr(NO) 3 9H 2 O was dissolved in 40 mL of deionized water to obtain a metal salt solution. 5 mmol of terephthalic acid was evenly dispersed in 4 mL of N,N-dimethylformamide to obtain an organic solution. The metal salt solution and the organic solution were mixed and stirred, and hydrofluoric acid was added dropwise while stirring. 3 9H 2 O was added dropwise with 3.8 μl of hydrofluoric acid. After the addition was completed, the mixture was heated at 170°C for 18 h. After cooling to room temperature, the solvent was removed by filtration. The obtained green solid product was dispersed in deionized water and centrifuged. The deionized water washing and centrifugation were repeated three times. The obtained solid product was placed at 70°C for reaction for 3 h. After cooling to room temperature, the solvent was removed by centrifugation. The solid product was dispersed in DMF and centrifuged. It was dried at 80°C to obtain MIL-101 (Cr).

[0052] (2) Preparation of MIL-101(Cr)@Ni 3 (HHTP) 2 Compound

[0053] A mixed solvent was prepared according to a volume ratio of deionized water to n-propanol of 1:1. 5 mmol of 2,3,6,7,10,11-hexahydroxytriphenylene and 20 mmol of MIL-101(Cr) were dissolved in 150 mL of the mixed solvent, and 9 mL of N,N-dimethylacetamide was added dropwise, and ultrasonication was performed for 25 min to obtain solution A.

[0054] 5mmol Ni(CH 3 COO 2 ·4H 2 O was dispersed in 80 mL of the mixed solvent and mixed by ultrasonication to obtain solution B.

[0055] Solution A and solution B were mixed, stirred at 65 °C for 4 h, cooled to room temperature, and centrifuged to remove the solvent. The obtained dark blue solid was dispersed again in 100 mL of mixed solvent, and 5 mmol 2,3,6,7,10,11-hexahydroxytriphenylene and 5 mmol Ni(CH 3 COO 2 ·4H 2O, 9 mL of N,N-dimethylacetamide was added dropwise, ultrasonicated for 6 min and allowed to stand for 10 min, then stirred at 60 °C for 3 h, cooled to room temperature, centrifuged to remove the solvent, and the obtained solid product was washed three times with deionized water and acetone, respectively, and dried at 80 °C to obtain a blue-black solid MIL-101(Cr)@Ni 3 (HHTP) 2 Composite, namely MOF composite.

[0056] Example 3

[0057] The preparation method of the MOF composite with light-to-heat conversion performance of this embodiment is as follows:

[0058] (1) Preparation of MIL-101(Cr)

[0059] Weigh 5mmol Cr(NO) 3 9H 2 O was dissolved in 40 mL of deionized water to obtain a metal salt solution. 5 mmol of terephthalic acid was evenly dispersed in 5 mL of N,N-dimethylformamide to obtain an organic solution. The metal salt solution and the organic solution were mixed and stirred, and hydrofluoric acid was added dropwise while stirring. 3 9H 2 O was added dropwise with 4.0 μl of hydrofluoric acid. After the addition was completed, the mixture was heated at 160°C for 20 h. After cooling to room temperature, the solvent was filtered to remove the solvent. The obtained green solid product was dispersed in deionized water and centrifuged. The deionized water washing and centrifugation were repeated three times. The obtained solid product was placed at 70°C for reaction for 3 h. After cooling to room temperature, the solvent was removed by centrifugation. The solid product was dispersed in DMF and centrifuged. It was dried at 80°C to obtain MIL-101 (Cr).

[0060] (2) Preparation of MIL-101(Cr)@Ni 3 (HHTP) 2 Compound

[0061] A mixed solvent was prepared according to a volume ratio of deionized water to n-propanol of 1:1. 5 mmol of 2,3,6,7,10,11-hexahydroxytriphenylene and 20 mmol of MIL-101(Cr) were dissolved in 150 mL of the mixed solvent, and 9 mL of N,N-dimethylacetamide was added dropwise, and ultrasonication was performed for 20 min to obtain solution A.

[0062] 5mmol Ni(CH 3 COO 2 ·4H 2 O was dispersed in 80 mL of the mixed solvent and mixed by ultrasonication to obtain solution B.

[0063] Solution A and solution B were mixed, stirred at 60 °C for 4 h, cooled to room temperature, and centrifuged to remove the solvent. The obtained dark blue solid was dispersed again in 100 mL of mixed solvent, and 5 mmol 2,3,6,7,10,11-hexahydroxytriphenylene and 5 mmol Ni(CH 3 COO 2 ·4H 2 O, 9 mL of N,N-dimethylacetamide was added dropwise, ultrasonicated for 8 min and allowed to stand for 10 min, then stirred at 60 °C for 4 h, cooled to room temperature, centrifuged to remove the solvent, and the obtained solid product was washed three times with deionized water and acetone, respectively, and dried at 80 °C to obtain a blue-black solid MIL-101(Cr)@Ni 3 (HHTP) 2 Composite, namely MOF composite.

[0064] Example 4

[0065] The preparation method of the MOF composite with light-to-heat conversion performance of this embodiment is as follows:

[0066] (1) Preparation of MIL-101(Cr)

[0067] Weigh 5mmol Cr(NO) 3 9H 2 O was dissolved in 50 mL of deionized water to obtain a metal salt solution. 5 mmol of terephthalic acid was evenly dispersed in 6 mL of N,N-dimethylformamide to obtain an organic solution. The metal salt solution and the organic solution were mixed and stirred, and hydrofluoric acid was added dropwise while stirring. 3 9H 2 O was added dropwise with 4.4 μl of hydrofluoric acid. After the addition was completed, the mixture was heated at 180°C for 12 h. After cooling to room temperature, the solvent was filtered to remove the solvent. The obtained green solid product was dispersed in deionized water and centrifuged. The deionized water washing and centrifugation were repeated three times. The obtained solid product was placed at 80°C for reaction for 5 h. After cooling to room temperature, the solvent was removed by centrifugation. The solid product was dispersed in DMF and centrifuged. It was dried at 80°C to obtain MIL-101 (Cr).

[0068] (2) Preparation of MIL-101(Cr)@Ni 3 (HHTP) 2 Compound

[0069] A mixed solvent was prepared according to a volume ratio of deionized water to n-propanol of 1:1. 5 mmol of 2,3,6,7,10,11-hexahydroxytriphenylene and 20 mmol of MIL-101(Cr) were dissolved in 200 mL of the mixed solvent, 10 mL of N,N-dimethylacetamide was added dropwise, and ultrasonication was performed for 30 min to obtain solution A.

[0070] 5mmol Ni(CH 3 COO 2 ·4H 2 O was dispersed in 100 mL of mixed solvent and mixed by ultrasonic to obtain solution B.

[0071] Solution A and solution B were mixed, stirred at 70 °C for 5 h, cooled to room temperature, and centrifuged to remove the solvent. The obtained dark blue solid was dispersed again in 100 mL of mixed solvent, and 5 mmol 2,3,6,7,10,11-hexahydroxytriphenylene and 5 mmol Ni(CH 3 COO 2 ·4H 2 O, 10 mL N, N-dimethylacetamide was added dropwise, ultrasonicated for 10 min and allowed to stand for 10 min, then stirred at 65 °C for 5 h, cooled to room temperature, centrifuged to remove the solvent, and the obtained solid product was washed three times with deionized water and acetone, respectively, and dried at 80 °C to obtain a blue-black solid MIL-101(Cr)@Ni 3 (HHTP) 2 Composite, namely MOF composite.

[0072] The MOF composite of the present invention was subjected to the following performance tests: MIL-101(Cr), MIL-101(Cr)@Ni 3 (HHTP) 2 The complexes are all from Example 3.

[0073] In the following examples, Ni 3 (HHTP) 2 The preparation method is as follows:

[0074] 0.06 mmol HHTP (19.46 mg) was added to 4 mL of a mixed solvent of N,N-dimethylformamide (DMF) and deionized water in a volume ratio of 1:1, and ultrasonicated for 10 min; 0.12 mmol Ni(CH 3 COO 2 ·4H 2 O (29.86 mg) was dissolved in 2 mL of deionized water and ultrasonicated for 10 min. The two solutions were mixed and transferred to a 20 mL sealed glass bottle and heated in a blast oven at 80 ° C for 24 h. After cooling to room temperature, the solvent was removed by centrifugation and the solid product was redispersed in deionized water, DMF, ethanol, and acetone, and the solvent was removed by centrifugation. The process was repeated three times, and finally dried in an oven at 80 ° C for use to obtain Ni 3 (HHTP) 2 .

[0075] (1) For Ni 3 (HHTP) 2 and MIL-101(Cr), MIL-101(Cr)@Ni in Example 3 3 (HHTP) 2 The composite was scanned by electron microscope. The scanning results are shown in Figure 1 , Figure 1 (a) is Ni 3 (HHTP) 2 (b) is the electron microscope scanning result of MIL-101(Cr) crystal, (c) and (d) are both MIL-101(Cr)@Ni 3 (HHTP) 2 Scanning electron microscope results of the complex. Figure 1 It can be seen that Ni 3 (HHTP) 2 The MIL-101(Cr) nanoparticles have a regular octahedral morphology and a smooth surface. 3 (HHTP) 2 The composite has a core-shell structure, with the surface of the octahedral MIL-101(Cr) core covered by a layer of Ni 3 (HHTP) 2 The nanorods are covered with these rod-shaped crystals, which are tightly attached to the surface of the MIL-101(Cr) core.

[0076] (2) Using MIL-101(Cr)@Ni of Example 3 3 (HHTP) 2 The composite was used as a sample to test its full XPS spectrum. The results are shown in Figure 2 .from Figure 2 It can be seen that the peaks at 284 and 532 eV of binding energy belong to the signal peaks of C and O elements respectively, the peaks at 577 and 689 eV of binding energy belong to the signal peaks of Cr 2p and Cr 2s respectively, and the peak at 858 eV of binding energy belongs to the signal peak of Ni 2p. Figure 2 MIL-101(Cr)@Ni 3 (HHTP) 2 The compounds all contain the four elements mentioned above.

[0077] (3) Using MIL-101(Cr)@Ni of Example 3 3 (HHTP) 2 The composite was used as a sample to analyze MIL-101(Cr)@Ni 3 (HHTP) 2 Complex with Ni 3 (HHTP)2 High-resolution Ni 2p in crystals 3 / 2 The results are shown in Figure 3 .from Figure 3 It can be seen that MIL-101(Cr)@Ni 3 (HHTP) 2 Complex with Ni 3 (HHTP) 2 The spectra of the crystals are basically consistent, indicating that in MIL-101(Cr)@Ni 3 (HHTP) 2 The coordination environment of Ni ions in the complex is similar to that of pure Ni 3 (HHTP) 2 The coordination environment in the crystal is the same.

[0078] (4) Measurement of Ni 3 (HHTP) 2 , MIL-101(Cr) and MIL-101(Cr)@Ni of Example 3 3 (HHTP) 2 N of the complex 2 The isothermal adsorption-desorption curve shows Figure 4 .from Figure 4 It can be seen that MIL-101(Cr)@Ni 3 (HHTP) 2 The curve of the composite is similar to that of MIL-101(Cr). Compared with MIL-101(Cr), MIL-101(Cr)@Ni 3 (HHTP) 2 The specific surface area of ​​the composite is 2768m 2 g –1 Down to 2381m 2 g –1 .

[0079] (5) Using nonlinear density functional theory to calculate the pore size distribution of the material, the results are as follows Figure 5 As shown, from Figure 5 It can be seen that MIL-101(Cr)@Ni 3 (HHTP) 2 The pore sizes of the composite are mostly 1.1 and 1.5 nm for micropores and 3.1 nm for mesopores. Compared with MIL-101(Cr), there are 1.9 nm more micropores. This is due to the Ni 3 (HHTP) 2 The XPS is caused by the introduction of N 2 The specific surface area and pore size distribution data obtained by adsorption calculation can indirectly prove that Ni 3 (HHTP) 2Successful synthesis on the surface of MIL-101(Cr) crystal.

[0080] (6) MIL-101(Cr)@Ni was tested using a vapor adsorption analyzer (BelmaxⅡ, Bayer, Japan). 3 (HHTP) 2 The water vapor static isothermal adsorption-desorption curve of the composite is shown in Figure 6 .from Figure 6 It can be seen that MIL-101(Cr)@Ni 3 (HHTP) 2 The water adsorption curve of the composite is similar to that of MIL-101(Cr), both of which are step-shaped, and both inflection points appear at P / P 0 Compared with MIL-101(Cr), MIL-101(Cr)@Ni 3 (HHTP) 2 The first rising point of the composite adsorption curve shifts to the left, P / P 0 When it is 0.4, its saturated adsorption capacity is 0.4 gg –1 , which is four times that of MIL-101(Cr), indicating that MIL-101(Cr)@Ni 3 (HHTP) 2 The composites are more hydrophilic and have stronger water adsorption application potential at moderate humidity.

[0081] (7) The dynamic adsorption tester of steam (BSD-DVS, Beijing Best) was used to measure the relative humidity of 40%, 60% and 80% respectively. 3 (HHTP) 2 The adsorption rate of the complex is shown in the test results. Figure 7 .from Figure 7 It can be seen that the greater the relative humidity, the higher the MIL-101(Cr)@Ni 3 (HHTP) 2 The shorter the time required for the composite to reach adsorption saturation, the faster its average adsorption rate. When the relative humidity is 40%, the composite still does not reach saturation after 240 minutes of adsorption, while when the relative humidity is 80%, it can reach water adsorption equilibrium within 100 minutes.

[0082] (8) MIL-101(Cr)@Ni was tested using a UV-visible-near infrared spectrophotometer (Shimadzu UV-3600i Plus, Shimadzu, Japan) 3 (HHTP) 2 The reflectivity of the composite in the full sunlight spectrum range is calculated according to the following formula:

[0083] A=1-RT

[0084] Wherein, R is reflectivity (%), and T is transmittance (%).

[0085] The absorbance test results are shown in Figure 8 .from Figure 8 It can be seen that MIL-101(Cr)@Ni 3 (HHTP) 2 The composite exhibits strong absorption capacity in the entire solar light band, ranging from 70% to 90%.

[0086] In addition, a xenon lamp (CME-SL500, Beijing Zhongke Micro Energy) was used to simulate sunlight in an indoor environment, and an infrared thermal imager (TES-132, Taiwan TES Electronics Industry) was used to record the MIL-101(Cr)@Ni 3 (HHTP) 2 The maximum temperature of the composite surface changes with time. The results are shown in Fig. 9 .from Fig. 9 It can be seen that after the light source is turned on, MIL-101(Cr)@Ni 3 (HHTP) 2 The surface temperature of the composite material rose rapidly, reaching 66°C after 200s, and reached equilibrium at 90.2°C when the illumination time was 800s.

[0087] (9) Common MOF (MOF-801, MOF-303) and MIL-101(Cr) purchased from the market, as well as MIL-101(Cr)@Ni 3 (HHTP) 2 The composite was used as a sample and the thermal conductivity was tested. The results are shown in Fig.10 .from Fig.10 It can be seen that MIL-101(Cr)@Ni 3 (HHTP) 2 The thermal conductivity of the composite is much higher than that of common MOF (MOF-801, MOF-303). Therefore, during the thermal desorption process, the heat can be transferred to MIL-101(Cr)@Ni 3 (HHTP) 2 Composite crystal and MIL-101(Cr)@Ni 3 (HHTP) 2 The efficient transfer between the complex crystals improves the overall water desorption efficiency. The computer automatically reads and records the value of the balance, and the desorption amount m(gg –1 ) and desorption efficiency η(%):

[0088]

[0089] In the formula, m s is the mass of the complex when it reaches adsorption saturation, m i is the initial mass of the dry composite, m r is the mass of the composite after desorption.

[0090] MIL-101(Cr)@Ni 3 (HHTP) 2 The results of the change of the desorption amount of the composite over time are shown in Fig.11 .from Fig.11 It can be seen that under light conditions, MIL-101(Cr)@Ni 3 (HHTP) 2 The mass of the complex decreases rapidly, and the desorption amount is calculated to be 0.58 gg within 800 s. –1 The desorption efficiency is 83%, indicating that MIL-101(Cr)@Ni 3 (HHTP) 2 The composite has excellent light absorption, light-heat conversion and heat conduction properties.

[0091] (10) To explore the MIL-101(Cr)@Ni 3 (HHTP) 2 To test whether the composite has the stability and cyclic regeneration ability as an adsorption bed in the water extraction device, an adsorption / photothermal desorption cycle experiment was carried out. 3 (HHTP) 2 Spread it on a watch glass, cover it with filter paper and make sure it forms a uniform thin layer of about 1 mm by lightly pressing it, and place it on an electronic balance to accurately monitor the mass change during adsorption and desorption. The composite was exposed to air for 11 hours in a laboratory environment with a temperature of 18-33 °C and a relative humidity of 40%-60%, and then the xenon lamp was turned on and the light intensity was set to 1 kW m –2 Irradiate it, observe and record the water desorption of the complex within 1 hour of illumination, and complete a complete adsorption-desorption cycle. During the test, MIL-101(Cr)@Ni 3 (HHTP) 2 The relationship between the water adsorption of the composite and time is shown in Fig.12 .from Fig.12 It can be seen that the adsorption saturated MIL-101(Cr)@Ni 3 (HHTP) 2 The composite can reach desorption equilibrium in less than 30 minutes, and the calculated desorption efficiency is 82.8%. In the subsequent adsorption-desorption cycle, the photothermal desorption efficiency is stable at 90%. Fig.13After multiple cycles of testing, MIL-101(Cr)@Ni 3 (HHTP) 2 It not only exhibits excellent water adsorption capacity, but also demonstrates efficient photothermal desorption performance, while demonstrating its outstanding cycle stability.

[0092] Therefore, the MOF composite with light-to-heat conversion performance of the present invention can be used in adsorption-type air water extraction.

[0093] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.

Claims

1. A MOF composite with light-to-heat conversion performance, characterized in that: The MOF composite is a core-shell structure with MIL-101 (Cr) as the core and Ni3 (HHTP)2 nanorods as the shell, and the Ni3 (HHTP)2 nanorods are attached to the MIL-101 (Cr) particles.

2. The MOF composite with light-to-heat conversion performance according to claim 1, characterized in that: The MIL-101 (Cr) is an octahedral crystal structure with a smooth surface.

3. The MOF composite with light-to-heat conversion performance according to claim 1, characterized in that: The MOF composite includes the following preparation raw materials: MIL-101(Cr), 2,3,6,7,10,11-hexahydroxytriphenylene and Ni(CH3COO)2·4H2O, and the molar ratio of MIL-101(Cr), 2,3,6,7,10,11-hexahydroxytriphenylene and Ni(CH3COO)2·4H2O is 2:1:

1.

4. A method for preparing a MOF composite having light-to-heat conversion performance, characterized in that: The following steps are involved: Weigh 2,3,6,7,10,11-hexahydroxytriphenylene and MIL-101(Cr) respectively, dissolve them in a mixed solvent consisting of deionized water and n-propanol, drop N,N-dimethylacetamide into it, and perform ultrasonication for 10 to 30 minutes to obtain solution A; Disperse Ni(CH3COO)2·4H2O in a mixed solvent consisting of deionized water and n-propanol, and mix by ultrasonication to obtain solution B; Solution A and solution B were mixed, stirred at 55-70°C for 2-5 hours, cooled to room temperature, and centrifuged. The obtained solid was dispersed in the mixed solvent again, and 2,3,6,7,10,11-hexahydroxytriphenylene and Ni(CH3COO)2·4H2O were added. N,N-dimethylacetamide was added dropwise, and ultrasonic treatment was performed for 5-10 minutes. Subsequently, the mixture was stirred at 50-65°C for 2-5 hours, cooled to room temperature, and centrifuged. The obtained solid product was washed three times with deionized water and acetone, respectively, and dried to obtain a MOF composite.

5. The method for preparing the MOF composite with light-to-heat conversion performance according to claim 4, characterized in that: The total molar ratio of the MIL-101(Cr), 2,3,6,7,10,11-hexahydroxytriphenylene and Ni(CH3COO)2·4H2O is 2:1:

1.

6. The method for preparing a MOF composite having light-to-heat conversion performance according to claim 4, characterized in that: In the mixed solvent, the volume ratio of deionized water to n-propanol is 1:

1.

7. The method for preparing a MOF composite having light-to-heat conversion performance according to claim 4, characterized in that: The preparation method of the MIL-101(Cr) is as follows: Cr(NO)3·9H2O is weighed and dissolved in deionized water to obtain a metal salt solution, terephthalic acid is uniformly dispersed in N,N-dimethylformamide to obtain an organic solution, the metal salt solution and the organic solution are mixed and stirred, and hydrofluoric acid is added with stirring, and heated at 150-180°C for 12-24 hours. After cooling to room temperature, the solvent is filtered out, and the obtained solid product is dispersed in deionized water, placed at 60-80°C for reaction for 2-4 hours, cooled to room temperature, centrifuged to remove the solvent, and then washed with DMF and dried to obtain MIL-101(Cr).

8. The method for preparing the MOF composite with light-to-heat conversion performance according to claim 7, characterized in that: The molar ratio of Cr(NO)3·9H2O to terephthalic acid is 1:

1.

9. The method for preparing the MOF composite with light-to-heat conversion performance according to claim 7, characterized in that: 18-22 mL of hydrofluoric acid is added dropwise for each mole of Cr(NO)3·9H2O.

10. Use of the MOF composite according to any one of claims 1 to 3 or the MOF composite prepared by the preparation method according to any one of claims 4 to 9 in adsorption-type air water extraction.